Analisis Keabsahan Kontrak Elektronik dalam Transaksi E-commerce: Persyaratan Hukum dan Implementasi dalam Era Digital Indonesia - David, David; Fakhlur, Fakhlur (Neolectura, 2024)
The rapid evolution of the digital era has significantly transformed societal behaviors, particularly in how transactions are conducted in Indonesia. As technological advancements permeate various life aspects, there's a growing reliance on electronic contracts, especially within e-commerce. This study delves into the legal standards and practical application of electronic contracts in Indonesia, exploring how they meet traditional contractual requirements like mutual consent, capacity, specified object, and lawful purpose as outlined in Article 1320 of the Indonesian Civil Code. The research employs a qualitative methodology, focusing on a comprehensive literature review to understand the existing legal frameworks and how they apply to electronic transactions. The analysis aims to bridge theoretical principles with real-world application, drawing from both primary and secondary sources to enrich the research findings. Results highlight that while electronic contracts facilitate efficiency and broader accessibility in transactions, there remain complexities in ensuring their validity and enforceability, particularly concerning the principles of good faith and contractual capacity. Significant legal interpretations still lean towards the necessity of written agreements despite the legal acceptance of electronic formats as binding agreements under Indonesian law. The study further observes a disparity in the legal recognition and practical application of electronic contracts, suggesting a need for clearer regulations and more robust consumer protection in the digital marketplace. Keywords: Electronic Contracts, E-commerce, Indonesian Civil Code, Contractual Law, Digital Transactions.